Finite Element Modeling of Headform Impactor Crash with Laminated Windshield - Kosiński, Piotr; Osiński, Jerzy (Journal of Applied Nonlinear Dynamics, 2026)
The main object of the present study is to investigate the mechanical behavior of laminated car windshield in the case of a pedestrian head impact. Windshield Finite Element model consist one layer o f P VB and two layer s of glass. The layer of P VB was modeled in a few cases: as elastic, elasto-plastic, "low-density foam" and hyper elastic material model. The layers of glass we remodeled as "brittle cracking" material model included in Abaqus simulation environment. Both of layers was modeled as solid. Examined also two type of PVB mesh elements: " 3 D Stress " and " Cohesive ". In addition, consideration was two types of connection between glass and PVB layers: first merge and second tie connection. Analysis was performed with different types of mesh. Radial mesh proved to be better than rectangular mesh to reflect the phenomenon of cracking glass. Furthermore, the peak value of the head form linear acceleration has been tested for different thickness and material models of PVB layer.